Gas Flaring and Venting : A Regulatory Framework and Incentives for Gas Utilization - Gerner, Franz (World Bank, Washington, DC, 2012)
Every year oil producers flare and vent gas equivalent to the combined gas consumption of Central and South America. Africa flares and vents gas equivalent to half its power consumption. To reduce this practice, governments need to develop and enforce an appropriate legal and regulatory framework. They need to reform the gas market, getting rid of subsidies for competing fuels and making room for private operators to develop gas infrastructure. And they need to avoid tax and royalty systems that discourage operators from using the gas associated with oil production.